Mediating effect of workers attitude on relationship between OSHMS and OSH culture at construction industry - Giall Banan @ John Banan (2020)
The construction industry is crucial to any country. Especially developing countries like Malaysia. However, a fatal accident is always associated with construction work. Therefore, the Malaysian government has enacted the Acts, namely OSHA 1994 and CIDBA 1994 and has established the departments of DOSH and CIDB. DOSH is acted as an enforcement body to ensure the contractors are complying with the OSHA 1994. CIDB is responsible for contractors' development and the construction personnel. Both are providing a free consultation to contractors for the improvement of OSH management system in the work sites. Both also urged the contractors to adopt the proper OSH management system such as OHSAS 18001. With government support, enforcement bodies, and a systematic OSH management system should have shaped the OSH culture. The workers' attitudes should have more matured in addressing and controlling the hazards and risks and other OSH issues in the construction sites. Accidents at construction sites should be controllable and not an issue of concern to everyone. Nevertheless, accidents are still occurring in construction sites. Adopting positivism research philosophy and quantitative method, therefore, this study was conducted in Sarawak. The aimed of this study was to investigate the mediation effect of the workers' attitudes on the relationship between OSH management system elements and OSH culture. The OSH management system elements would include the OSH policy, HIRARC, role and responsibility, training, site inspection, and management review as independent variables, workers' attitude would be the mediator, and the OSH culture was the dependent variable. The survey questionnaires were distributed to seven (7) on-going projects. There were (5) on-going construction sites located in the City of Kuching and two (2) on-going construction sites located in the district of Bintulu. The study showed the mediation effect of workers' attitude on the relationship between OSH management system elements and the OSH culture especially the elements of HIRARC, role and responsibility, and the OSH training. This study also showed the direct effect between the OSHMS especially the HIRARC, role dan responsibility, and the safety training and the workers' attitude, and between the workers' attitude and the OSH culture.